2012
DOI: 10.1007/s00011-011-0421-7
|View full text |Cite
|
Sign up to set email alerts
|

Sodium caseinate induces mouse granulopoiesis

Abstract: CasNa induces granulopoiesis with functional granulocytes, suggesting that this molecule could be an innate immune system activator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
(60 reference statements)
0
9
0
2
Order By: Relevance
“…Interestingly, Domínguez-Melendez et al showed that administration of casein as sodium caseinate in BALB/c mice increased the percentage of myeloid precursors from bone marrow and increased the total number of bone marrow leukocytes resulting from cell proliferation. They also found that casein induced proliferation and activation of granulocytes, and it increased the serum concentration of cytokines such as G-CSF, M-CSF, and GM-CSF [37]. These cytokines are key to the proliferation, differentiation, and activation of granulomonocytic cells, which in turn induce multiple functions within the immune response; since these cytokines regulate inflammation, as is the case for monocyte-macrophages, they are responsible for phagocytosis, which is a crucial event in fungal and bacterial infections; once activated, macrophages are the bridge between activated CD4+ lymphocytes and the adaptive immune response [38].…”
Section: Casein and Hematopoietic Tissuementioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, Domínguez-Melendez et al showed that administration of casein as sodium caseinate in BALB/c mice increased the percentage of myeloid precursors from bone marrow and increased the total number of bone marrow leukocytes resulting from cell proliferation. They also found that casein induced proliferation and activation of granulocytes, and it increased the serum concentration of cytokines such as G-CSF, M-CSF, and GM-CSF [37]. These cytokines are key to the proliferation, differentiation, and activation of granulomonocytic cells, which in turn induce multiple functions within the immune response; since these cytokines regulate inflammation, as is the case for monocyte-macrophages, they are responsible for phagocytosis, which is a crucial event in fungal and bacterial infections; once activated, macrophages are the bridge between activated CD4+ lymphocytes and the adaptive immune response [38].…”
Section: Casein and Hematopoietic Tissuementioning
confidence: 93%
“…On the other hand, the Santiago-Osorio group showed that the IP inoculation of BALB/c mice with sodium caseinate induces in vivo proliferation of the myeloid lineage in the bone marrow. Interestingly, it was observed that the granulocytes had the ability to incorporate BrdU, a thymidine analyte that is incorporated into proliferating cells; further, the cells exhibited a greater ability to phagocytose when compared to cells from mice that had not received treatment [37].…”
Section: The Role Of Caseins In Granulopoiesis and Monocytopoiesismentioning
confidence: 99%
“…Una vez obtenida la sangre de los ratones, se centrifugó durante 10 minutos a 1.500 rpm para obtener el suero. Posteriormente, se evaluó la concentración de IL-7 en el suero, respetando el procedimiento del kit de ELISA (Mouse Interleukin 7, Immunoassay, R&D Systems, MN, USA) durante las dos horas posteriores al sacrificio (6). La lectura de las placas se realizó a 450 nm en un espectrofotómetro Tecan (Tecan Spectra, Austria).…”
Section: Detección De Citocinasunclassified
“…Nuestro grupo de trabajo demostró que, mediante la inyección de caseinato de sodio, se induce la granulopoyesis en médula ósea, y se incrementan los niveles séricos del factor estimulante de colonias de granulocitos (Granulocyte Colony-Stimulating Factor, G-CSF) y del factor estimulante de colonias de granulocitos y monocitos (GranulocyteMacrophage Colony-Stimulating Factor, GM-CSF) (6). El caseinato de sodio es un agente proinflamatorio capaz de actuar sobre células de origen hematopoyético y, también, incrementa las concentraciones de citocinas con un rol fundamental en la mielopoyesis (7).…”
unclassified
“…It is widely known that inoculation of sodium caseinate (CasNa), a salt of casein, the principal milk protein [ 11 ], induces the accumulation of granulocytes and macrophages in the peritoneal cavity of mice and increases the serum levels of cytokines related to HSC mobilization [ 3 , 12 , 13 ]. In this regard, we recently showed that granulocyte activation by CasNa, which resembles stimulation by G-CSF or GM-CSF [ 14 ], increases spleen size, weight, and cellularity [ 15 – 17 ]. This suggests extramedullary hematopoiesis activation, which may involve migration of HSC or HPC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%